(untitled) (American Journal of Islam and Society, 2009)
This article seeks to explain and analyze the concept of cultural ikhtilaf (difference) in the Qur’an. Islam introduces a model for human communication among cultures at the individual and group levels that is based on human values that guarantee a person’s dignity and human rights. The principle of difference in Islam means accepting the “other,” namely, the different person, by establishing relations based on acquaintance, dialogue, sharing, and reciprocity. Difference became an important conceptual tool in the framework of traditional Muslim societies’willingness to accept diversity and has remained an important part of Muslim discourse.1 The different person is not a mere independent isolated unit living within his/her own world and whose main concern is to protect himself/herself and his/her identity from loss and forgetfulness. Rather, he/she is characterized by his/her communicative and productive nature and entity, which are delineated by mutual dependence on the “other” while maintaining the independence of the “other.” The “other” also has an independent and confident character that qualifies him/her to establish a communicative and reciprocal relationship that seeks to achieve public advantage. The “different” person can prove his/her truth, since “difference” is used in a saying based on evidence,2 and the established truth based on this evidence grants its holdermoral and logical confidence, therebymaking him/her more open to the “other.” In addition, evidence indicates the power of argumentative logic and high epistemological level of those who differentiate. The concept of difference, while based on rationality and logic, also carries a moral dimension as a complementary unity.As a result, therefore, difference turns out to be a fundamental element in establishing a civilized creative society ...